the Design Of Donut Ordering Information System To Expand Website-Based Market Share (WEB) (Case Study On UD Brandan Donuts): Perancangan Sistem Informasi Pemesanan Donat untuk Memperluas Pangsa Pasar Berbasis Website (WEB) (Studi Kasus pada UD Brandan Donuts) - Nanda, Sri Handayani; Nadya, Yusri; Irawan, Heri (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2022)
Brandan Donuts is a business that is engaged in the culinary field, especially delicious and healthy snacks, namely donuts. UD Brandan Donuts was founded by Jumardani, on September 1, 2015, at Jalan Sisingamangaraja, Simpang Limun, Medan City. The problem with UD Brandan Donuts is that the ordering and marketing system still relies on media for direct interaction with consumers (buyers) which makes it difficult for the management to expand market share. The purpose of this research is to build an order information system using the DFD method and apply the design of an online ordering information system at UD Brandan Donuts (WEB). The research uses the data flow diagram (DFD) method to design the system flow and uses the implementation of a software program, Xampp in designing a website (WEB). The results on the website design there are 2 levels that will run in ordering donuts online, namely Level 1 consisting of the buyer login process, ordering, delivery, admin login, financial reports. And level 2 consists of the process of registering a buyer's account, logging in, selecting a donut product, filling in order data, selecting the type of transaction, payment, confirmation of order completion, delivery schedule, order confirmation until, input of donut category, input of donut stock, confirmation of order data, confirmation payment, promotion, daily report processing, monthly report processing, and annual report processing. The conclusion in this research is that the context diagram design contains 6 entities and for the data flow diagram (DFD) design it has a level of 2.17 and as many as 22 flowcharts. And produce a website (WEB) that displays an admin page, buyer page and courier page to make it easier for consumers (buyers) to order online.